Interaction of rat glutathione S-transferases 7-7 and 8-8 with gamma-glutamyl- or glycyl-modified glutathione analogues. - Adang, A E (1989)
Analogues of GSH in which either the gamma-glutamyl or the glycyl moiety is modified were synthesized and tested as both substrates for and inhibitors of glutathione S-transferases (GSTs) 7-7 and 8-8. Acceptor substrates for GST 7-7 were 1-chloro-2,4-dinitrobenzene (CDNB) and ethacrynic acid (ETA) and for GST 8-8 CDNB, ETA and 4-hydroxynon-trans-2-enal (HNE). The relative ability of each combination of enzyme and GSH analogue to catalyse the conjugation of all acceptor substrates was similar with the exception of the combination of GST 7-7 and gamma-L-Glu-L-Cys-L-Asp, which used CDNB but not ETA as acceptor substrate. In general, GST 7-7 was better than GST 8-8 in utilizing these analogues as substrates, and glycyl analogues were better than gamma-glutamyl analogues as both substrates and inhibitors. These results are compared with those obtained earlier with GSH analogues and GST isoenzymes 1-1, 2-2, 3-3 and 4-4 [Adang, Brussee, Meyer, Coles, Ketterer, van der Gen & Mulder (1988) Biochem. J. 255, 721-724] and the implications with respect to the nature of their active sites are discussed.